Ultrastructural morphologic description of the wild rice species Oryza latifolia (Poaceae) in Costa Rica - Sánchez, Ethel; Montiel, Mayra; Espinoza, Ana (Revista de Biología Tropical, 2003)
The wild rice species Oryza latifolia is endemic to Tropical America, allotetraploid and has a CCDD genome type. It belongs to the officinalis group of the genus Oryza. This species is widely distributed throughout the lowlands of Costa Rica and it is found on different life zones, having great morphologic diversity. The purpose of this research is to perform a morphologic description of O. latifolia samples of three Costa Rican localities (Carara, Liberia and Cañas) and to see if the phenotypic diversity of the species is reflected at the ultrastructure level. Structures such as the leaf blade, ligule, auricles and spikelet were analyzed. Leaf blade morphology of the specimens from the three localities is characterized by the presence of diamond-shaped stomata with papillae, zipper-like rows of silica cells; a variety of evenly distributed epicuticular wax papillae and bulky prickle trichomes. The central vein of the leaf blade from the Cañas populations is glabrous, while those from Carara and Liberia have abundant papillae. There are also differences among the borders of the leaf blade between these locations. Cañas and Liberia present alternating large and small prickle trichomes ca. 81 and 150 μm, while Carara exhibits even sized prickle trichomes of ca. 93 μm. Auricles from Cañas are rectangular and present long trichomes along the surface ca. 1.5 mm, while those of Liberia and Carara wrap the culm and exhibit trichomes only in the borders. The ligule from the plants of Carara has an acute distal tip, while that of Cañas and Liberia is blunt. The Liberia spikelet has large lignified spines while Cañas and Carara show flexible trichomes.